UID2022. DIALOGUES. Visions and Visuality. 43rd International Conference of Representation Disciplines Teachers (diségno, 2022)
1992-2022: after thirty years, the UID annual Conference returns to Genoa, the “Lerici Conference” –as it was  defined– returns home, but in a different house: from the usual appointment in the splendid setting of La Spezia Riviera, to the headquarters of the Architecture and Design department in the town center, attended on the occasion of the celebrations organized by Genoa for the 500th anniversary of the discovery of America following the voyage of Columbus.This is the reasoning starting point to identify themes and objectives of the meeting, from the deeply changed relationship of the University with the host context and from the dialogue that today’s University is gradually establishing with society in a deeper and deeper and more incisive way. [read more]